"Для проискания себѣ к житие мѣста пришел в город": дитина і наймитування в міському суспільстві гетьманщини ХVІІІ ст. - Сердюк, І. (Місто: історія, культура, суспільство, 2017)
У статті досліджується використання найманої дитячої праці суспільством Гетьманщини з наголосом на її особливостях, притаманних для міського населення. Наймана праця та учнівство означали перебування дитини за межами власної родини та мобільність (у рамках одного населеного пункту, або ж на більшій території). Така трудова міграція дітей та підлітків була важливою складовою виокремлення міста Гетьманщини над округою. В його населенні, порівняно із селами, підвищена концентрація осіб віком 10–14, а найбільше – 15–19 років. Міста пропонували більше варіацій винагороди. Вони мали розмаїття вакансій і пропозицій роботи саме для малолітніх та неповнолітніх слуг. Концентруючи економічні та людські ресурси, місто Гетьманщини давало можливість знайти роботу десь поблизу з рідною домівкою. Дитина могла кілька разів змінювати господарів, однак не покидаючи одного населеного пункту. В сільській місцевості, такі переміщення відбувалися б від хутора до хутора, чи поміж селами. Переваги міста невіддільні від його небезпек, адже соціальний капітал, набутий малолітніми наймитами, міг бути і негативним та поширюватися на всю родину. Наявність мігрантів, мандрівного та маргіналізованого елементу, солдати на постої – ці типово міські явища породжували попит на проституцію, куди втягувалися малолітні дівчата. Хлопчиків могли залучати до крадіжок худоби та речей, підманювати до втеч, викрадати для служби. У такому разі родини дітей-наймитів не тільки не отримували користі із заробітків своїх нащадків, але ще й наражалися на іншування, мусили сплачувати шкоду і так далі. Попри ці небезпеки місто Гетьманщини вабило до себе молодь. The article examines the use of hired child labor in the Hetman State society with an emphasis on its peculiarities inherent to the urban population. In general, the labor was the most important element of the socialization of the child at the time, and it worked “seriously”; its work was aimed precisely at the outcome but not at the process or work itself. This is the main difference from the present-day practices, and that is what made possible and allowed the widespread use of hired child labor, it was regarded not as a upbringing, but as a real contribution to the family economy. The child could make a contribution to the family economy by working directly in the family economy, as well as by working beyond it. At the same time, many kinds of work done, its volume, character, etc. could be similar. At the same time, the work of the son of the artisan on the one hand and his pupil on the other, or the same daughter of the Cossack and his young tenant, bore distinctly different social contexts. Hired labor and apprenticeship meant having a child outside his own family and stated his mobility (within a single settlement or on a larger territory). Such labor migration of children and adolescents was an important part of the separation of the Hetman State city over its district. The concentration of people aged 10-14, and most notably of 15-19 years increased in its population in comparison with villages. Cities offered more variations of the rewards. They had more variety of vacancies and job offers specifically for minors. By concentrating economic and human resources, the Hetman State city gave an opportunity to find work somewhere close to their homes. The child could change the owners several times, but without leaving that same settlement. In rural areas, such migrations took place from farm to farm, or between villages. This state of affairs created a system of competition between the hirelings for good work and between employers for the good hirelings. The mechanisms of such competition, as well as inequality and discrimination related to the work of children, are the problem of a separate study. The city’s advantages are inseparable from its dangers, because the social capital acquired by young minors could be negative and extend to the whole family. The presence of migrants, the traveling and marginalized elements, the soldiers on the posts – all of these, typically urban phenomena, gave birth to the demand for prostitution, in which young girls were involved. The boys could be involved in the theft of livestock and things, to fend for fleeing, to steal for service. In this case, the families of hired children not only did not benefit from the earnings of their descendants, but also suffered from the use of equipment, had to pay for damage, and so on. Despite these dangers, the city of Hetman State attracted young people. When exploring hired labor in the early modern days, it is worth abandoning the Soviet approach, which considers it mainly as one-sided operation. At present, the most productive is the concept of life cycle service or life cycle servanthood. From this point of view, the service of the house (in Ukrainian historiography labeled with the concept of “hiring” (Ukr. ‘naymy’, ‘naymytuvannya’) does not appear as something permanent, accomplished, but as one of the stages of human life, an important component of its socialization. It is considered not only as a consequence of poverty, but as a certain fuse from this phenomenon, which allowed to survive elementary, to obtain a certain social capital, to acquire some material resources necessary for the transition to the next stage of the life cycle.